In silico Investigation on Clopidogrel, Prasugrel and Ticagrelor as Potential Mono Antiplatelet Therapy for Acute Coronary Syndrome - Hibatullah, Muhammad Naufal; Suryono, Suryono; Rachmania, Sheilla (Cell and BioPharmaceutical Institute, 2024)
Background: In acute coronary syndrome (ACS), antiplatelet therapy is crucial for inhibiting platelet aggregation. Dual antiplatelet therapy (DAPT) commonly employs aspirin along with clopidogrel, prasugrel, or ticagrelor. This is well known that aspirin acts as a cyclooxygenase (COX)-1 inhibitor, while clopidogrel, prasugrel, and ticagrelor act as P2Y12 inhibitors. Despite DAPT's proven efficacy in more effectively reducing cardiovascular events in ACS patients, this is associated with an increased risk of bleeding compared to mono antiplatelet therapy (MAPT). To minimize the cost and side effect that might arise from the use of DAPT, this is necessary to assess the potential of MAPT using a P2Y12 inhibitor drug, to understand whether they are capable of binding to both COX-1 and P2Y12. Hence, this study was conducted to identify P2Y12 inhibitor drugs that have the ability to bind to COX-1, allowing them to be proposed as MAPT.Materials and methods: Molecular docking was employed to assess binding affinity, interaction types, amino acid residues, binding distances, and visualizations in both 3D and 2D formats. The applications utilized were BIOVIA Discovery Studio and AutoDock, while the websites utilized were research collaboratory for structural bioinformatics protein data bank (RCSB PDB) and PubChem.Results: In silico findings reveal differences in binding strength among clopidogrel, prasugrel, and ticagrelor to COX-1 and P2Y12, with ticagrelor emerging as the stronger ligand due to a higher number of bindings and/or closer binding distances. Notably, only prasugrel and ticagrelor demonstrate the ability to bind to the active site of COX-1.Conclusion: Therefore, prasugrel and ticagrelor emerge as potential MAPT agents for ACS patients.Keywords: clopidogrel, prasugrel, ticagrelor, antiplatelet, ACS, in silico, molecular docking